A self-powered biosensing system based on triboelectric nanogenerator for rapid bacterial DNA detection - Qu, Xiaolin; Qi, Peng; Wang, Peng; Li, Jiawei; Wang, Congyu; Zhang, Dun; Wan, Yi; Ai, Shiyun; Wang, Xiaoqiang (Sensors and actuators. B, Chemical, 2023)
A self-powered biosensing system based on triboelectric nanogenerator (TENG) for bacterial DNA detection is invented and a vertical contact-separation TENG was designed to provide a steady power supply to a detection bioreactor. A carboxyl-functionalized capture probe was modified on etched indium tin oxide (ITO) glass, with which target bacterial DNA could be recognized. Meanwhile, multi-walled carbon-nanotubes (CNT)-modified signal probe was designed to amplify the detection signal due to its excellent electrical conductivity. The self-powered biosensing system could measure the variation in output voltage and be highly sensible with a low detection limit at 0.084 pM of target DNA. In addition, a mathematical model based on the Freundlich isotherm was built to simulate the DNA detection process, and it was feasible to simulate the calibration equation and detection range. A portable self-powered biosensing device was made by integrating miniaturized TENG and bioreactor in a 3D-printed mold, with which the presence of bacterial DNA could be instantly indicated by LED (light-emitting diode). This study provided a useful platform for quick bacterial DNA detection and paved the way for further development of pocket diagnosis with TENG-based biosensing systems. •A self-powered DNA biosensor system based on TENG to detect 16 S rDNA of bacteria.•A mathematical model of DNA concentration detection based on the Freundlich isotherm.•Self-powered DNA biosensor system has a wide detection range and low detection limit.•Detection result can be directly indicated by a portable TENG device through LED.